Biomarkers of exposure - Smith, Thomas (Henry Stewart Talks, 2007)
Biomarkers as indicators of exposure, adverse effects or susceptibility for an individual, Methods of exposure: inhalation, ingestion or skin absorption, Toxicokinetics as a guide to understanding biomarker behaviour, Calibration of biomarkers, Example of using biomarkers for exposure to MTBE in gasoline, Using a physiologically based toxicokinetic (PBTK) model of MTBE to estimate tissue and biomarker levels, Metabolic gene-environment interaction in biomarker production, Using lab exposures to study biomarkers and the dose-response relationship
Archived at 2016/06/22